THE INFLUENCE OF RICE PRODUCTION, INTERNATIONAL RICE PRICES, POPULATION, AND GROSS DOMESTIC PRODUCT (GDP) ON INDONESIA'S RICE IMPORTS - Sydney Zaneta; Anak Agung Ketut Ayuningsasi (Adisam Publisher, 2025)
Trade plays a crucial role in a country's economic activities. The intensity of a country's trade activities serves as an indicator of its people's prosperity and as a benchmark for its economic level. Through trade, a country can establish diplomatic relations with neighboring countries. Indonesia's import activities are part of the government's policy in the field of international trade. The discrepancy between production levels and societal demand is one of the primary reasons for implementing an import trade policy. This study aims to analyze the influence of rice production, international rice prices, population, and GDP on rice imports in Indonesia from 1993 to 2023. This research employs a quantitative approach using time-series data spanning 31 years. The data used in this study is secondary time-series data analyzed through multiple linear regression (OLS) and the Error Correction Model (ECM). The Vector Error Correction Model (VECM) method is applied because the data is stationary at the first difference level and exhibits cointegration. The findings indicate that, based on ECM estimates, all variables under study tend to move toward equilibrium (cointegrated) in the long run. In both the short and long term, rice production, international rice prices, population, and GDP collectively influence rice imports in Indonesia. However, in the short term, these variables do not significantly affect rice imports. The long-term partial estimation results show that rice production and international rice prices have a statistically significant positive effect on Indonesia's rice imports. Meanwhile, population has a positive but statistically insignificant effect, and GDP has a negative but statistically insignificant effect on Indonesia's rice imports from 1993 to 2023.